ANALISIS KETIMPANGAN PEMBANGUNAN ANTAR KABUPATEN/KOTA DI SUMATERA BARAT DAN KEBIJAKAN PENANGGULANNYA - Bakri, Bakri; Syafrizal, Syafrizal; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2015)
This study aims to analyze and determine the effect of: (1) economic growth for development inequality between districts / cities in West Sumatra, (2) investment towards development gaps between districts / cities in West Sumatra, (3) labor for development inequality between counties / town in West Sumatra and (4) fund balance to inequality of development between districts / cities in West Sumatra. This type of research is descriptive and associative. While this type of data is data documentary, source of data is secondary data as well as data-shaped panel (combined data time series and cross-section). This research use analysis tool with Ordinary Least Squared (OLS). The study concluded that (1) Economic growth significant and positive impact on the inequality of development of West Sumatra province. (2) Investment inequality affects development of West Sumatra province significantly and positively. (3) Workers not significant impact on the inequality of development of West Sumatra province. (4) The fund balance inequality influence the development of West Sumatra province significantly and positively. Based on these results the policies that can be suggested is to increase government spending on productive expenditure such as construction of a strategic business region in order to increase the amount of capital investment as development.Â Keyword : development inequality, economic growth, invesment, labor, fund balance